2020
DOI: 10.3390/vaccines8020327
|View full text |Cite
|
Sign up to set email alerts
|

Trends, Coverage and Influencing Determinants of Influenza Vaccination in the Elderly: A Population-Based National Survey in Spain (2006–2017)

Abstract: Influenza is a significant public health problem and the elderly are at a greater risk of contracting the disease. The vaccination coverage of the elderly is below the Spanish target of 65% for each influenza season. The aims of this study were to report the coverage of influenza vaccination in Spain among the population aged ≥65 years and high-risk groups for suffering chronic diseases, to analyze the time trends from 2006 to 2017 and to identify the factors which affect vaccination coverage. A nationwide cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 70 publications
1
21
0
Order By: Relevance
“…Regarding marital status, we found that being separated or divorced decreased the vaccination uptake. This result is consistent with the ndings of the study that found that being widowed increased the decision to become immunized while being separated or divorced decreased it [45]. Despite some authors found no relationship between those variables, marital status is considered an important predictor of healthcare utilization.…”
Section: Discussionsupporting
confidence: 90%
“…Regarding marital status, we found that being separated or divorced decreased the vaccination uptake. This result is consistent with the ndings of the study that found that being widowed increased the decision to become immunized while being separated or divorced decreased it [45]. Despite some authors found no relationship between those variables, marital status is considered an important predictor of healthcare utilization.…”
Section: Discussionsupporting
confidence: 90%
“…A remarkable result of our investigation is that, in contrast to the COPD population, total vaccination uptake among non-COPD women was significantly higher than among non-COPD men. Higher uptake by women than by men in the general population was reported in many, but not all, investigations conducted in Spain [ 42 , 43 , 44 , 45 , 46 , 47 ]. In our country, previous studies showed that uptake may be mediated by age, with better rates for males among those aged ≥65 years and for females among those under this age [ 45 ].…”
Section: Discussionmentioning
confidence: 89%
“…Regarding the age of vaccination, most of the studies carried out in Spain [ 42 , 43 , 44 , 45 , 46 , 47 , 50 , 51 ] and in other countries, such as the United States, Canada, Germany, and other European regions [ 24 , 52 ], agree that in individuals older than 64 years, the probability of vaccination is higher than in the younger groups [ 30 , 50 ]. So, in the study carried out by Saeed et al, a vaccination rate of only 44.8% was achieved in COPD patients aged between 40 and 64 years [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with those described in the literature. Age and number of chronic conditions were positively associated with vaccination against influenza and pneumococcal diseases in Belgium [20] and Spain [21] in at-risk groups. Similarly, patients with COPD, HIV, and solid organ transplantation (SOT) were more likely to be vaccinated against influenza and pneumococcal diseases than patients with heart failure.…”
Section: The Vaccine Uptake In France and Europe And Associated Factorsmentioning
confidence: 96%